KAJIAN IMPLEMENTASI KEBIJAKAN ORGANISASI KESATUAN PENGELOLAAN HUTAN (KPH) DI DAERAH (STUDI KASUS KPH BANJAR, KALIMANTAN SELATAN DAN KPH LALAN MANGSANG MENDIS, SUMATERA SELATAN) - Elvida Yosefi Suryandari; Sylviani Sylviani (Jurnal Analisis Kebijakan Kehutanan, 2012)
Forest Management Units (FMUs) establishment has been laid as a strategic objective to better management of forests. However, problems are still encountered in the development of FMUs, such as institutional framework of its funding and human resources avaibility. This study aims to: (1) analyze the policy implementation of FMU organization; and (2) analyze the availability of human resources in FMU development. The study was conducted in Lalan Mangsang Mendis FMU, South Sumatra Province and Banjar FMU, South Kalimantan Province. The data were collected using purposive sampling and analyzed using human resource planning analysis and policy analysis. The results showed that the current form of FMU organization is a technical implementation unit of "Regional Working Unit" (RWU) of Forestry Office. There is an incompatibility of the structure with the organizational structure of the existing regulation. The organization model has some weaknesses, such as limitations of budget and authority, and lack of human resources (quantity and quality). Regional Working Unit (RWU) form could consist of a secretariat, a service unit, technical unit (TU), or other working unit as part of the regency organizations. Regional Working Unit (RWU) form that is compatible for FMU should be TU or other working unit. According to article 45 on PP 41/2007, FMU organizations should not be inform of ”TU” but may bean" other working unit", because the existing organization components already reached a maximum score. The current priority should be how to strengthen the FMU institution as "Regional Working Unit" (RWU) with a good planning. Important steps are still needed before the operation of FMU, such as how to determine the role and function of FMU and working relationships with relevant stakeholders including forest license holders, which then should be arranged in the form of regulations. Further, the commitment of local government is needed to support the formation of a FMU as RWU.